2013
DOI: 10.1051/0004-6361/201322276
|View full text |Cite
|
Sign up to set email alerts
|

A metallicity study of 1987A-like supernova host galaxies

Abstract: Context. The origin of the blue supergiant (BSG) progenitor of Supernova (SN) 1987A has long been debated, along with the role that its sub-solar metallicity played. We now have a sample of SN 1987A-like events that arise from the rare core collapse (CC) of massive (∼20 M ) and compact ( 100 R ) BSGs. Aims. The metallicity of the explosion sites of the known BSG SNe is investigated, as well as the association of BSG SNe to starforming regions. Methods. Both indirect and direct metallicity measurements of 13 BS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(94 citation statements)
references
References 66 publications
(121 reference statements)
3
91
0
Order By: Relevance
“…To estimate the Z at the location of our SNe within their hosts, we can correct the global Z of their hosts for the metallicity gradient that is known to characterize galaxies (e.g., Pilyugin et al 2004;Taddia et al 2013Taddia et al , 2015, where the nucleus is typically more metal-rich than the outer parts. We used the derived global Z as a proxy of the central Z, and then adopted an average Z gradient of −0.47 R −1 25 (see Pilyugin et al 2004).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…To estimate the Z at the location of our SNe within their hosts, we can correct the global Z of their hosts for the metallicity gradient that is known to characterize galaxies (e.g., Pilyugin et al 2004;Taddia et al 2013Taddia et al , 2015, where the nucleus is typically more metal-rich than the outer parts. We used the derived global Z as a proxy of the central Z, and then adopted an average Z gradient of −0.47 R −1 25 (see Pilyugin et al 2004).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We also include unpublished values from the CALIFA survey, which will be presented in Galbany et al Kuncarayakti et al (2013a,b), Inserra et al (2013), and Taddia et al (2013b) 3 . Our final sample is of 245 CC SN host H ii region oxygen abundances.…”
Section: Host H II Region Metallicitiesmentioning
confidence: 99%
“…SNe IIn, observations suggest that mass-loss occurred close to the epoch of explosion, causing the large dispersion in properties observed in this class (see e.g. Kiewe et al 2012;Taddia et al 2013b). Deciphering which changes in progenitor properties link to changes in SN features is then a key question.…”
Section: Introductionmentioning
confidence: 99%
“…Among the major classes of CC SNe (II, Ib, and Ic), SNe Ib and Ic tend to occur in high-metallicity regions compared to SNe II (Anderson et al 2010), although the difference of the site metallicities of type Ib and Ic SNe is still a matter of debate (Modjaz et al 2011;Leloudas et al 2011;Sanders et al 2012b;Kuncarayakti et al 2013). It is also suggested that metallicity plays an important role in the occurrence of some subclasses of CC SNe (Modjaz et al 2011;Sanders et al 2012a;Taddia et al 2013;Lunnan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of supernova remnant (SNR) searches, Matonick & Fesen (1997) have shown that the observed number density of SNR is higher in nearer galaxies, because it becomes easier to resolve a confused region in a galaxy when it is nearby. We can expect that our capability to investigate the explosion site of a transient event would depend on the distance to the event (e.g., Sanders et al 2012bSanders et al , 2013Taddia et al 2013), as in the cases of SNR searches.…”
Section: Introductionmentioning
confidence: 99%